Nitrogen uptake in lentil cultivar mixtures is not predictable from pure stands performance but is correlated with agronomic parameters and experimental conditions - Lorenzetti, Elisa; Carlesi, Stefano; Michelsen, Anders; Bàrberi, Paolo (Agriculture & food security, 2024)
BackgroundIn the context of rising costs of raw materials and environmental degradation caused by livestock farming, the agri-food sector faces significant challenges in sourcing sustainable proteins. Grain legumes have emerged as cost-effective protein sources, with lower water footprint and GHG emissions compared to animal sources. However, their cultivation is threatened by strong yield fluctuations. Leveraging intra-specific diversity through cultivar mixtures in cropping systems can effectively buffer biotic and abiotic stresses, hence increasing yield stability. In this study, we investigate the effect of intra-specific diversity on lentil nitrogen uptake under pot (2020) and field conditions (2021). We hypothesize that cultivars with higher affinity for nitrogen fixation influence the other components of the mixture, and that nitrogen uptake dynamics are a possible driver in modulating cultivar mixture behaviour. We designed two-, three-, and four-cultivar mixtures with a trait-blind approach and compared them to sole cultivars.Results and conclusionsOur results show inconsistencies across the two experimental years, indicating that lentils may shift their nitrogen source from the atmosphere to the soil when grown in pots. Mixtures 15N enrichment was not always consistent with pure stand performance, suggesting that cultivar mixtures may have an unpredictable cumulative effect on nitrogen uptake. Regarding correlations with agronomic parameters, we observed a significant correlation between nodules number and nitrogen concentration, regardless of experimental conditions. Finally, we found that 15N excess emerged as a significant predictor for pure stands’ yield, but the differences were diluted with the increase in diversity levels. The findings on 15N enrichment responses, cultivar impacts, and complex mixture effects on soil microbiota underscore the need for further research.